Integration of ATAC-Seq and RNA-Seq Identifies Key Genes in Light-Induced Primordia Formation of Sparassis latifolia - Yang, Chi (Int J Mol Sci, 2019)
Light is an essential environmental factor for Sparassis latifolia primordia formation, but the molecular mechanism is still unclear. In this study, differential expression profiling of light-induced primordia formation (LIPF) was established by integrating the assay for transposase accessible chromatin by sequencing (ATAC-seq) and RNA-seq technology. The integrated results from the ATAC-seq and RNA-seq showed 13 down-regulated genes and 17 up-regulated genes in both the L vs. D and P vs. D groups, for both methods. According to the gene ontology (GO) annotation of these differentially expressed genes (DEGs), the top three biological process categories were cysteine biosynthetic process via cystathionine, vitamin B6 catabolic, and glycine metabolic; the top three molecular function categories were 5-methyltetrahydropteroyltriglutamate-homocysteine S-methyltransferase activity, glycine binding, and pyridoxal phosphate binding; cellular component categories were significantly enriched in the glycine cleavage complex. The KEGG (Kyoto Encyclopedia of Genes and Genomes) enrichment analysis revealed that these genes were associated with vitamin B6 metabolism; selenocompound metabolism; cysteine and methionine metabolism; glycine, serine, and threonine metabolism; and glyoxylate and dicarboxylate metabolism pathways. The expression of most of the DEGs was validated by qRT-PCR. To the best of our knowledge, this study is the first integrative analysis of ATAC-seq and RNA-seq for macro-fungi. These results provided a new perspective on the understanding of key pathways and hub genes in LIPF in S. latifolia. It will be helpful in understanding the primary environmental response, and provides new information to the existing models of primordia formation in edible and medicinal fungi.